Caracterización y democratización de la educación superior en Mercosur ampliado - Álvarez, María Franci Sussan (2019)
1. Fundamentación; 2. Argentina; 3. Brasil; 4. Chile; 5. Colombia; 6. Paraguay; 7. Paraguay